Best care for older people with epilepsy: A scoping review. (February 2021) - Wojewodka, Gabriella; McKinlay, Alison; Ridsdale, Leone
Highlights: Older people with epilepsy lack information to self-manage and few have care plans. Older people with epilepsy report more mental health symptoms than their peer group. CBT was trialled for older people and found to reduce seizure frequency. Older people are referred less to neurology services than those under 60. Geriatricians and GPs could contribute to more care for epilepsy with extra training. Abstract: There are two peaks of diagnosis of epilepsy: in childhood and in people over 65. Older people may have complex needs like co-morbidity, polypharmacy, frailty, and social isolation. This scoping review focusses on the care of older people with epilepsy beyond diagnosis and medical treatment. We sought to identify areas within the UK health service needing development either in clinical practice or through further research. The search returned 4864 papers with 33 papers included in the review. The papers were grouped into psychosocial, self-management and services themes. Only one randomised controlled trial was found. Research was mainly based on cohort and case-control studies. Older people require more information to self-manage epilepsy and more psychological support to help with symptoms of anxiety and depression. People reported experiencing stigma and a reluctance to disclose their condition. This may increase the risk of isolation and difficulties in managing epilepsy. Studies reported that older people are referred less to neurologists, suggesting there may be a gap in care provision compared to younger people. Generalist health professionals may be better placed to provide holistic care, but they may need additional training to alleviate uncertainties in managing epilepsy. Care plans could help provide information, particularly for co-morbidity, but few had one. Our findings highlight psychological and self-management needs for managing epilepsy in older people. Health service staff may require upskilling to shift epilepsy management from neurologists to generalists. More research is needed regarding psychological and self-management interventions, particularly in the form of randomised controlled trials.